Landuse culture and water quality (BOD, COD, DO) in the upper citarum river corridor - Setiawan Iwan; Rohmat Dede; Ismail Arif; Suhendro Suhendro (E3S Web of Conferences)
The culture of land use in river corridors has a major effect on water quality, especially on organic chemical parameters such as BOD, COD and DO. This complexity is the main attraction to study in depth. The objectives of this study include several points to analyze (1) the correlation between land use culture and water quality (BOD, COD and DO); (2) constructing a strategy for handling water quality pollution in the upper Citarum river corridor. The method used was a survey with a regional approach through geospatial and correlation analysis. The results obtained (1) Water quality (BOD, COD and DO) has a strong correlation with anthropogenic activities of land use culture around the river corridor such as settlements, industry, chemical fertilizer use and others. (2) Handling strategies that are tailored to the identified zones such as forest areas, builtup areas, agriculture and shrubs. Some of the research results obtained can be used as relevant references for targeted treatments to succeed in a sustainable fragrant Citarum.